Feasibility of closing nutrient cycles from black water by microalgae-based technology - Silva, Gustavo H.R. [UNESP]; Sueitt, Ana Paula E.; Haimes, Sarah; Tripidaki, Aikaterini; van Zwieten, Ralph; Fernandes, Tânia V. (Elsevier, 2019)
Microalgae can recover macronutrients and trace elements from wastewaters. The microalgae biomass can then be used as fertilizer to enrich impoverished agricultural soils by increasing the soil´s carbon content and providing essential nutrients for soil health. Using microalgae for wastewater treatment will enable the shift from linear sanitation systems to circular ones where the carbon and nutrient cycles can be closed. By using a nutrient-rich wastewater medium for microalgae cultivation, high biomass productivity and, therefore, high nutrient recovery, can be achieved. In this study, we demonstrated that Chlorella sorokiniana and Chlorococcum sp. were able to grow in and remove nitrogen and phosphorus from anaerobically-digested black water (AnBW), in a 211 L tubular photobioreactor (PBR), placed in a temperature-controlled (25 °C) glass greenhouse, under Dutch natural light conditions (5.8 to 23.3 mol photons.m−2.d-1 and 67 to 270 μmol.s-1. m−2). The microalgae productivity varied from 0.13 g DW.L-1.d-1 (autumn) to 0.36 g DW.L-1.d-1 (summer). The nitrogen and phosphorus removal rates were 28 to 62 mg.L-l.d-1 and 2.3 to 5.4 mg.L-l.d-1, respectively. Due to the insufficient light availability for the high nitrogen and phosphorus concentrations of the AnBW cultivation medium (1280 mg.L-l and 68 mg.L-l, respectively), the overall nutrient removal efficiencies remained below 50% even during the summer period when light intensity was at its highest. Partial nitrification was confirmed by the accumulation of nitrite (≥ 1000 mg NO2-N.L-l) in the PBR. These high NO2 concentrations did not, however, hinder microalgae growth. The macronutrient and trace element compositions of the dry microalgal biomass were similar to commercially available organic fertilizers, indicating a potential for soil enrichment.
Keywords: Anaerobically-digested black water; Nitrifying bacteria; Nitrogen recovery; Organic fertilizer; Phosphorus recovery